2018
DOI: 10.1116/1.5042459
|View full text |Cite
|
Sign up to set email alerts
|

Tunable resistivity in ink-jet printed electrical structures on paper by plasma conversion of particle-free, stabilizer-free silver inks

Abstract: Printable metal inks are typically composed of premade nanoparticles that require postdeposition thermal sintering to produce crystalline, electrically conductive features. In this paper, it is shown that particle-free Ag inks made from simple, water-soluble metal salts such as silver nitrate can be ink-jet printed and converted into electrical features with tunable resistivity at low temperature (<100 °C) by exposure to a pure argon plasma. X-ray diffraction confirms that the converted inks are crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Another study showed that the conductivity of geometrically identical printed Ag structures could be systematically varied over a span of six orders of magnitude by adjusting plasma conductions such as power, background gas pressure, and duration. [ 28 ] The tunable resistance is attractive for small area resistors where changing the dimensions of the structure to achieve different resistances is challenging. Recently, the plasma‐activated conversion of printed ionic compounds was successfully extended to a large set of aqueous metal salt precursors, establishing a new class of particle‐free inks.…”
Section: Schemesmentioning
confidence: 99%
“…Another study showed that the conductivity of geometrically identical printed Ag structures could be systematically varied over a span of six orders of magnitude by adjusting plasma conductions such as power, background gas pressure, and duration. [ 28 ] The tunable resistance is attractive for small area resistors where changing the dimensions of the structure to achieve different resistances is challenging. Recently, the plasma‐activated conversion of printed ionic compounds was successfully extended to a large set of aqueous metal salt precursors, establishing a new class of particle‐free inks.…”
Section: Schemesmentioning
confidence: 99%
“…In practice, to achieve high sensitivity, the resistance of the thermistor at the reference temperature must be large. With the inorganic Ag-salt ink, in addition to the serpentine design, the resistance of the printed Ag line can be tuned by varying the plasma treatment time [16]. We found that for a line thickness of ~1 μm, plasma treatment at 150 W for 10 min yields Ag with a resistivity of 2 × 10 −6 Ω•m.…”
Section: Resultsmentioning
confidence: 97%
“…The thermistor was fabricated by the inkjet printing and plasma treatment process illustrated in Fig. 1(a) and first described in [16]. The Ag ink was prepared by dissolving 0.5 M (1.7 g) silver nitrate (AgNO 3 , 98% purity, Alfa Aesar) in a mixture of 4 ml de-ionized water (Millipore), and 16 ml ethylene glycol (Fisher Scientific).…”
Section: A Thermistor Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we report a new approach for inkjet printing based on particle‐free inks composed of inorganic metal salts and their conversion by a non‐equilibrium plasma to produce metallic structures at low temperatures (<138 °C). Plasmas have been previously applied to reduce metal salts to common noble metals such as Au, Ag, Pd, and Pt . Our study expands this technology to enable a library of metals, including both noble metals such as Au, Ag, Pd, and Pt and non‐noble metals such as Cu, Pb, Bi, and Sn, to be printed by a single process that involves plasma reduction of the printed structure.…”
Section: Introductionmentioning
confidence: 99%